Effects of dual-task training in patients with post-stroke cognitive impairment: A randomized controlled trial - Sun, Ruifeng; Li, Xiaoling; Zhu, Ziman; Li, Tiancong; Zhao, Man; Mo, Linhong; Li, Wenshan; Xi, Xiaoshuang; Huang, Peiling; Gong, Weijun (Frontiers in Neurology, 2022)
Background Evidence for the efficacy of cognitive-motor dual-task (CMDT) training in patients with post-stroke cognitive impairment (PSCI) and no dementia is still lacking. More importantly, although some studies on the cognitive effect of CMDT training show an improvement in cognitive performance, the results are still controversial, and the intervention mechanism of CMDT training on cognitive function improvement is not clear. The main purpose of this study was to analyze the effects of CMDT training on cognitive function, neuron electrophysiology, and frontal lobe hemodynamics in patients with PSCI. Methods Here we tested the effects of CMDT training on cognitive function in PSCI patients. Forty subjects who met the criteria of PSCI were randomly assigned to control and experimental groups. CMDT training or cognitive task (CT) training was administered to each patient in the experimental and control groups, respectively. All subjects performed Mini-mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) scale before and after the intervention, and the event-related potentials (ERP) and functional near-infrared spectroscopy (fNIRS) were used to evaluate the changes in neuron electrophysiology and hemodynamics. Results Forty patients were randomized across Beijing Rehabilitation Hospital Capital Medical University in Beijing. At the end of the intervention, 33 subjects completed the experimental process. The CMDT group showed significant improvement in the MMSE (P = 0.01) and MoCA (P = 0.024) relative to the CT group. The results of ERP and fNIRS showed that CMDT training could shorten the latency of P300 (P = 0.001) and the peak time of oxygenated hemoglobin (P = 0.004). The results showed that CMDT training shortened the response time of central neurons and significantly increased the rate of oxygen supply to the frontal lobe. Conclusion CMDT training in patients with PSCI improved global cognitive function, which was supported by the improved neural efficiency of associated brain areas. Clinical trial registration http://www.chictr.org.cn, identifier ChiCTR2000034862.